PENERAPAN MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI INFORMASI - Safitri, Nadya; Ardiansyah, Andri; Fahri , Muhammad (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Education is the spearhead of a country's progress, with the quality of education being the key to determining the direction of national development. Developed and developing countries often realize the importance of education as a top priority for development. The development of information technology, especially in the world of education, has a significant impact on the learning process. According to Subdibyo Lies (2020), the development of information technology brings positive changes in the world of education, making learning more efficient and effective. In Indonesia, in accordance with Law No. 20 of 2013 concerning National Education Objectives, education aims to educate the nation's life, and one way to achieve this is through the use of technology in learning. E-learning as a form of educational technology offers various benefits, such as interactivity, independence, accessibility, and enrichment of learning. Although the implementation of e-learning in Indonesia is still uneven, this technology has great potential to advance the education system, including in Islamic religious education learning. This study aims to explore the application of information technology-based learning media at SMP Yameba Cimulang, as well as the challenges faced in its implementation. The results of the study are expected to provide an overview of the effectiveness of the use of technology in Islamic religious learning and its contribution to improving the quality of education in the school